1999
DOI: 10.1902/jop.1999.70.7.752
|View full text |Cite
|
Sign up to set email alerts
|

Density of CD1a‐Labeled Langerhans' Cells in Normal Human Gingiva and in Nifedipine‐ and Immunosuppressive Medication‐Induced Gingival Overgrowth

Abstract: The reduced numbers of CD1a-labeled cells found in nifedipine-induced gingival overgrowth were similar to the reduced numbers of CD1a-labeled cells in gingival overgrowth associated with immunosuppressive medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[4][5][6] It has been previously reported that CsA and nifedipine medication affect numbers of Langerhans cells 7 and macrophages 8,9 in overgrown gingiva and may play roles in qualitative changes in inflammatory response. Dihydropyridines are calcium-channel blocking agents often taken by patients with cardiovascular disorders and undergoing organ transplantation.…”
mentioning
confidence: 99%
“…[4][5][6] It has been previously reported that CsA and nifedipine medication affect numbers of Langerhans cells 7 and macrophages 8,9 in overgrown gingiva and may play roles in qualitative changes in inflammatory response. Dihydropyridines are calcium-channel blocking agents often taken by patients with cardiovascular disorders and undergoing organ transplantation.…”
mentioning
confidence: 99%
“…The number of CD1a+ dendritic cells in the sulcular and junctional/pocket epithelia and in the LP in areas which had an inflammatory infiltrate were significantly less in subjects who were immunosuppressed compared to the subjects who were healthy. A previous study 13 had also evaluated the number of CD1a+ dendritic cells in the connective tissue and in the oral and sulcular and junctional epithelia of patients who were immunosuppressed compared to patients who were healthy, finding less CD1a+ dendritic cells in all the epithelia of the patients who were immunosuppressed. However, the authors did not describe a periodontal diagnosis for the patients who were healthy.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is not well understood but may be related to the modification of the immune response induced by the immunossupressive drug. An increased population of macrophages, cytotoxic‐T/sup‐pressor cells 10,11 and mononuclear and polymorphonuclear inflammatory cells, 12 and a decreased number of CD1a+ dendritic cells (DCs), 13 natural killer cells, 14 and mast cells 15 are found in the gingival tissue of patients medicated with cyclosporin A, nifedipine, or azathioprine. Azathioprine is another immunosuppressive drug used with cyclosporine‐A to prevent graft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…The drug may influence directly the inflammatory response by either affecting the nature of the cellular infiltrate or the release of cytokines, prostaglandins or growth factors (Nurmenniemi et al , 1999, 2002). Alternatively, the local inflammatory changes secondary to bacterial plaque may orchestrate the drug–fibroblast interaction (Seymour et al , 2000; Nurmenniemi et al , 2001).…”
Section: Introductionmentioning
confidence: 99%